Exploring the Spatially-Varying Effects of Human Capital on Urban Innovation in China - Lao, Xin; Gu, Hengyu; Yu, Hanchen; Xiao, Fan (Applied spatial analysis and policy, 2021)
This study employs city-level data from China to examine the spatially-varying effects of human capital on urban innovation, applying the multi-scale geographically weighted regression model to the knowledge production function. The results demonstrate that the effects of various determinants-including human capital, industrial structures, research and development investment, environmental quality, economic development levels-on innovation prompt different spatial patterns and ranges of influence, among which human capital significantly enhances the level of innovation with the strongest scale effects. Hence different policies should be formulated in cities of diverse conditions that are sensitive to their contexts.